The impact of social norms on entrepreneurial action: Evidence from the environmental entrepreneurship context - Meek, William R.; Pacheco, Desirée F.; York, Jeffrey G. (Journal of Business Venturing, 2010)
Using insights from institutional theory, sociology, and entrepreneurship we develop and test a model of the relationship between centralized and decentralized institutions on entrepreneurial activity. We suggest that both decentralized institutions that are socially determined as well as centralized institutions that are designed by governmental authorities are important in promoting firm foundings in the environmental context. In a sample of the U.S. solar energy sector we find that state-sponsored incentives, environmental consumption norms, and norms of family interdependence are related to new firm entry in this sector. Our findings also suggest that the efficacy of state-level policies in the sponsoring of entrepreneurial growth is dependent upon the social norms that prevail in the entrepreneur's environment. We expand entrepreneurship theory and the study of institutions and the natural environment by demonstrating the integral role that social norms play in influencing the creation of new firms and by illustrating the potential effect social norms have on the effect of policy that seeks to encourage environmentally responsible economic activity.